El Madrid de la Bestia : l’apocalypse urbaine d’Álex de la Iglesia - Diane Bracco (Cahiers de Civilisation Espagnole Contemporaine, 2014)
Far from being reduced to a simple setting, the Spanish capital plays an essential part in Álex de la Iglesia’s second full-length film, El día de la bestia, where it is represented as an organism consumed by violence. This article proposes an analysis of the variations on the apocalyptic theme, cornerstone of contemporary Madrid’s cinematographical portrait that the director paints in his movie. Through the deployment of strategies of grotesque distortion, de la Iglesia invites us to see in his filmic re-elaboration of the metropolis the metonymy of a Spain that has lost all its points of reference: while taking possession of the urban landscape, integrated into a spectacular production, de la Iglesia lifts the veil on the paradoxes of a postindustrial society which longs for modernization, at the dawn of the third millennium, although it still harbours the residues of a dictatorial past that the advent of democracy has not enabled to eradicate.